Green approach toward protection of secondary amine in pyrazole nucleus by PEG-400 and Boc catalyst - Suman Sharma, Amrita Verma, Rajani Chauhan, Rakhi Kulshrestha (Journal of Applied Pharmaceutical Science, 2020)
The objective of the present study is the protection of secondary amine in the substituted pyrazole derivative with the help of a green catalyst to facilitate the synthesis of anticancer compounds. Di-tert-butyl dicarbonate (Boc) has been used as a protecting agent with various catalysts such as Polyethylene glycols-400, Dimethyl aminopyridine, and N, N-Diisopropyl ethylamine. In this study, five different synthetic methods have been applied, but success has been achieved in only two. The very first method has been reported for the protection of secondary amine in pyrazole, associated with these catalysts. These synthetic methods had given a good yield and fewer side products, and it also a green approach toward synthetic chemistry.
Keywords: Di-tert-Butyloxycarbonyl, polyethylene glycol (PEG- 400), N,N-diisopropylethylamine, 4-dimethylamino pyridine.